One Phase Well Design for Minimum Drilling Cost at ZAZ Field - Kharisma Idea; Yaumil Hasbiyallah; Kesuma Ardhana Oerika; Muhammad Yusrin (Testing Center for Oil and Gas LEMIGAS, 2025)
Drilling cost components including rig, casing and accessories, well surface equipment, drilling mud, bits, cementing, and casing installation substantially influence the overall drilling cost. The One Phase Well (OPW) design is implemented by eliminating the surface casing, which is conventionally applied in casing designs for wells in the ZAZ Field. This study evaluates drilling parameters such as well data, well trajectory, pore pressure–fracture gradient, drilling time, material usage, and drilling costs. A well profile analysis is conducted to compare the Three Phase Well (TPW) and One Phase Well (OPW) designs. Analysis of drilling time, materials, and drilling costs is carried out to evaluate the cost reduction difference between the Three Phase Well (TPW) method and the One Phase Well (OPW) method.The OPW design reduces rig rental costs by 34.9%, bit costs by 53.9%, casing costs by 20.5%, wellhead costs by 8.7%, and mud costs by 3.7%. In contrast, cementing costs increase by 0.7%, and casing installation incurs an additional cost of USD 24,017. Overall, the total drilling cost difference between OPW and TPW amounts to USD 68,633, with OPW achieving a 12.7% reduction in overall drilling costs compared to TPW.